Urbanizing rural waters: Rural-urban water transfers and the reconfiguration of hydrosocial territories in Lima. (March 2017) - Hommes, Lena; Boelens, Rutgerd
Abstract: This article studies how urbanization processes and associated rural-urban water transfers in the Lima region (Peru) create water control hierarchies that align the municipal drinking water company, hydropower plants and rural communities on unequal positions. By scrutinizing the history of water transfers and hydropower development in the Lima region, the paper shows how imaginaries about the superiority of engineering, the need to generate electricity for national development, the backwardness of the 'land of lagoons' where water is diverted from, and about wished-for water abundance in Lima, all became manifested in hydraulic megaprojects. More than technical means to supply water to Lima City, these hydraulic grids, supported by legal, institutional and financial governance techniques; produce diverging material, social-symbolic and political effects for rural and urban water users. While the established system means water control and access for hydropower and drinking water companies, it implies dependence and/or exclusion from the benefits for rural communities. More specifically and beyond questions of outright water grabbing, perceived injustices involve the distribution of water-related benefits, loss of autonomy, and the socio-environmental impacts of territorial transformations. Highlights: Rural-urban water transfers originate from imaginaries of modernity and progress. Imaginaries, discourses and morals become cemented in concrete hydraulic systems. Transfers reconfigure hydrosocial territories physically, socially, symbolically. Legal-political configurations institutionalize highly political water transfers. Counter imaginaries contest claims of untapped resources and backward communities.